"I Do Not Speak as Freely": Gendered Views on Campus Carry at a Research University. Issue 4 (May 2023) - Somers, Pat; Gao, Huajian; Taylor, Z. W.
As campus carry policies are implemented at colleges and universities across the country, the concern for the safety of students, faculty members, and campus community members has heightened. In the state of Texas, broad sweeping campus carry policies were recently enacted by Texas State Legislature that allows individuals to conceal carry firearms within educational spaces on campus. Within these educational spaces, faculty members are often relied upon to deliver educational content without having their Second Amendment speech rights chilled by the prospect of loaded firearms within a classroom. Given this tension, this study fills an important gap in the research and explains how faculty members view campus carry as it relates to their personal safety and professional work. This study employed a mixed methods design (survey and qualitative) to expound upon the attitudes toward campus carry of 226 faculty and staff members working in a large research-intensive university within the state of Texas. Results suggest strong gender differences between how faculty members view campus carry policies and their safety on campus, with women often reporting feeling less safe and less able to perform their job duties under the pressure and anxiety of campus carry policies. Ultimately, this study's results imply that women faculty members may more less safe, more marginalized, and further victimized by campus carry laws than men faculty members, transgressing gender equity progress in the professoriate, as women have been traditionally underrepresented on college faculties.